Design and development of a home energy management system using wireless communications - Gan, Alvin Wei Keong (2013)
With the increase in energy cost, people starts pondering methods to monitor and maintain to reduce energy consumption. Good energy usage habits have to be promoted and utilizing energy efficiently will allow savings to electrical bills One of the ways is having a home automation system(HAS) The purpose of the HAS approach can help to provide real-time control and monitoring of individual appliance and find out which appliances consume energy the most.